Oral cancer epidemiology of Aurangabad district (Maharashtra) of India from 2005 to 2014: understanding the burden of disease - Niranjan, Vikram R.; Ranpise, Sudarshan G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral cancer incidence is constantly rising in India and is one of the major public health issues. This is a retrospective study from Aurangabad district (MS) of India to evaluate epidemiologic profile of oral cancer patients from 2005 to 2014. Methods: The 10 year data of oral cancer was obtained from the PCBR Aurangabad which was available from the National Cancer Registry Programme, Govt. of India web portal. The periodic data in three different spans was available as 2005 to 2008, 2009 to 2011 and 2012 to 2014. Statistical analysis used was age adjusted rate (AAR), crude rate (CR) and additive properties of CR. Results: The oral cancer trends from 2005 to 2014 reveals significantly increase in oral cancer incidence in population. In males, cancer of mouth (RP: 11.84% and AAR 7.37) was most common followed by tongue (RP: 9.62% and AAR 6.32) and pharynx (RP: 4.71% and AAR 2.79). In females cancer of tongue (RP: 3.31% and AAR 2.42) is most common followed by cancer of mouth (RP: 2.77% and AAR 1.91). Incidence of oral cancer as a whole for all sites is second highest after lung cancer in Aurangabad in male (cumulative AAR 17.93) and fourth highest after breast, cervix and lung cancer (cumulative AAR 6.06) in female out of all cancer sites in region in 2012-2014. Conclusions: Understanding pattern and incidence of various oral cancers is crucial for primary prevention and early detection for comprehensive management of cases.